2016
DOI: 10.1111/zsc.12182
|View full text |Cite
|
Sign up to set email alerts
|

The future of nemertean taxonomy (phylum Nemertea) — a proposal

Abstract: Turbeville, J.M. , Strand, M. (2016). The future of nemertean taxonomy (phylum Nemertea)a proposal. -Zoologica Scripta, 45: 579-582.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…1 3 Sundberg et al (2016a), as opposed to other authors (e.g. Gibson 1985;Roe et al 2007), proposed that histological features should not be included as a prerequisite to describe/ redescribe new nemertean fauna and that they instead should only be used to address questions about internal organ systems functionality and evolution.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 3 Sundberg et al (2016a), as opposed to other authors (e.g. Gibson 1985;Roe et al 2007), proposed that histological features should not be included as a prerequisite to describe/ redescribe new nemertean fauna and that they instead should only be used to address questions about internal organ systems functionality and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several internal characters used to differentiate between species and genera of nemerteans can sometimes show high levels of intraspecific variation (Envall and Sundberg 1993). In their manifesto, Sundberg et al (2016a) suggested that description and redescription of nemertean species should be accepted if they contain information about DNA sequences (at least cytochrome c oxidase -COI-), a description of the external characters including information on the ecology of the species, and type material of voucher specimens being fixed in preservatives ensuring future studies on the DNA of the species.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations